O gestor, o currículo e o itinerário formativo do professor: um diálogo entre a gestão e a formação - Souza, Claudia Xavier da Costa (2022)
The present dissertation raises the hypothesis of the educational paradigm of communication as a favorable way for the dialogue between the manager and teachers' professional development to take place. The general objective of this research is to analyze the construction of teachers' professional development itinerary based on the communication paradigm and, as specific objectives, to describe a professional development itinerary and to re-signify it from the conception of a critical curriculum. The research carried out is predominantly qualitative, it was developed in a pandemic period –Covid-19 –and based on the consultation of institutional documents and on the study of academic productions by classic and contemporary authors, among them: Dewey (1953, 1959);Freire (1987);Sacristán (1998);Schön (2000);Tardif (2019);Garcia (1992, 1999);L.Bondía (2002);Imbernón (2009, 2011);Cosme (2009, 2010);Nóvoa (2000);Lück ( 2008, 2009);Noffs (2003, 2018, 2019),who research on the topic. The analysis considered the years 2019, 2020 and 2021 and the professional development activities experienced by Middle School and High School teachers from a private school in São Paulo, based on the following categories of analysis: intentionality of action; awareness of the proposal; study and reflection; participation and sharing. Such categories are derived from the principles of the educational paradigm of communication. Their marked influence is characterized by the directparticipation of school management, being part of work groups and collaborating with the construction of teachers' professional development path. The highlights of this research were communication, authorship of thought, quality of interactions in the educational environment and the involved curricular flexibility through which we have a qualified, planned and articulated professional development itinerary that supports the teacher in his/her personal and professional development